Economic Growth in Indonesia during the COVID-19 Pandemic: Exports, Domestic Investment, and Government Expenditure: English - Beon, Julius Innosensius; Ramadhan, Ahmad Fajar; Listia, Listia; Afini, Nur (Economics Departement, Faculty of Business and Economics, Universitas Surabaya, 2026)
This study examines the impact of exports, domestic investment, and government expenditure on economic growth in Indonesia during the COVID-19 period (2020–2023). Using balanced panel data from 33 provinces, the analysis applies a Fixed Effects Model with Driscoll–Kraay standard errors to address heteroscedasticity, autocorrelation, and cross-sectional dependence. The results indicate that domestic investment and government expenditure have a positive and statistically significant effect on Gross Domestic Product (GDP), highlighting their critical role in supporting economic resilience during periods of crisis. Exports also exhibit a positive effect, although with weaker statistical significance, reflecting their vulnerability to global demand fluctuations and external shocks. In contrast, the COVID-19 pandemic has had a significant negative impact on economic growth, confirming the extent of economic disruption caused by the crisis. These findings underscore the importance of strengthening domestic economic drivers, particularly through investment promotion and effective fiscal policy, while reducing overreliance on external trade. Methodologically, this study contributes by employing a robust panel data approach that improves the reliability of estimation under complex data conditions. Overall, the study provides policy-relevant insights for enhancing economic stability and promoting sustainable recovery in the post-pandemic period.